Arms Length Bodies - Manning, Nick; Shepherd, Geoffrey (World Bank, Washington, DC, 2012)
There has always been a diversity of organizational forms within the public sector. However, in some countries organizational diversification has increased significantly through the distribution of government responsibilities to so-called "arm's-length bodies." This notion reflects their common characteristic of being at arm's length from the control of politicians, outside the hierarchical control of traditional vertically-integrated line ministries and departments. There is some uncertainty concerning the scale of this movement of staff and budgets towards such agencies. Some commentators maintain that arms-length agencies have always been found within governments and that some highly publicized examples of "agencification" have skewed the debate (Wettenhall 2005). Others argue that the creation of distinct entities with independent financial management regimes held responsible for discrete areas of service delivery is a distinct and growing phenomenon.